2006
DOI: 10.5688/aj7006128
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Utility of Nontraditional Test Scores for First-Year Pharmacy Student Academic Performance

Abstract: Objectives. To determine the value of employing the Learning and Study Strategies Inventory (LASSI), Defining Issues Test (DIT), and Watson-Glaser Critical Thinking Appraisal (WGCTA) in predictive models for first-year pharmacy student academic performance. Methods. Six years of pharmacy student admission and progression data were evaluated. Additional predictive validity offered by these variables over a model of prepharmacy grade point average and pharmacy college admission test (PCAT) score was examined. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…4,5 The LASSI has been used at more than 2274 academic institutions according to the LASSI publishers. 3 LASSI subtests have been demonstrated to be generalizable to different populations in higher education, including undergraduates, 4-6 pharmacy students, 7 and medical students. 8,9 Cano's recent indepth analysis 10 concludes that the LASSI remains an understudied instrument and more research is needed on its psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 The LASSI has been used at more than 2274 academic institutions according to the LASSI publishers. 3 LASSI subtests have been demonstrated to be generalizable to different populations in higher education, including undergraduates, 4-6 pharmacy students, 7 and medical students. 8,9 Cano's recent indepth analysis 10 concludes that the LASSI remains an understudied instrument and more research is needed on its psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…2,[7][8][9] Sleight and Mavis 9 examined LASSI subtest scores on a sample of 96 2nd-year medical students divided into low, medium, and high cohorts based on MCAT scores. The bottom cohort had the lowest scores and the top cohort had the highest scores on the Motivation and Concentration subtests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The PCAT is a standardized test designed to measure the abilities, aptitudes, and skills that pharmacy schools identify as essential for successful completion of their programs. 31 The test was developed in 1973 after a study conducted across American pharmacy schools confirmed that 82% were interested in a standardized entrance examination specific to pharmacy education. Since that time, the PCAT has been revised several times to incorporate pharmacy practice changes.…”
Section: Admissionsmentioning
confidence: 99%
“…For example, Lobb, Wilkin, McCaffrey, Wilson and Bentley (2006) found no predictive relation between university students' critical thinking skills and their first-year academic achievement.…”
mentioning
confidence: 99%